Pride and prejudice [videorecording (DVD)] - Leonard, Robert Z., 1889-1968; Garson, Greer, 1904-1996; Olivier, Laurence, 1907-1989; Boland, Mary, 1880-1965; O'Sullivan, Maureen, 1911-1998; Austen, Jane, 1775-1817 (Distributed by Warner Home Video, 2006)
The story of the five Bennet sisters living in early 19th century England. Their mother is scheming to make prestigious marriages for them. Focuses on Elizabeth Bennet, who mistakenly finds the rich Mr. Darcy an oaf, even as he sets all the other fair maidens' hearts aflutter.